Tidal volume challenge–induced hemodynamic changes can predict fluid responsiveness during one-lung ventilation: an observational study - Zhang, Yang; Ding, Yinyin; Zhang, Jiatong; Huang, Tianfeng; Gao, Ju (Frontiers in Medicine, 2023)
Background To evaluate the ability of tidal volume challenge (VTC)-induced hemodynamic changes to predict fluid responsiveness in patients during one-lung ventilation (OLV). Methods 80 patients scheduled for elective thoracoscopic surgery with OLV were enrolled. The inclusion criteria were: age ≥ 18 years, American Society of Anesthesiologists physical status I-III, normal right ventricular function, normal left ventricular systolic function (ejection fraction ≥55%), and normal or slightly impaired diastolic function. The study protocol was implemented 15 min after starting OLV. Simultaneous recordings were performed for hemodynamic variables of diameter of left ventricular outflow tract, velocity time integral (VTI) of aortic valve, and stroke volume (SV), and ΔSV-VTC, ΔVTI-VTC, and ΔMAP-VTC were calculated at four time points: with VT 5 mL/kg (T1); after VT increased from 5 mL/kg to 8 mL/kg and maintained at this level for 2 min (T2); after VT was adjusted back to 5 mL/kg for 2 min (T3); and after volume expansion (250 mL of 0.9% saline infused over 10–15 min) (T4). Patients were considered as responders to fluid administration if SV increased by ≥10%. Receiver operating characteristic (ROC) curves for percent decrease in SV, VTI, and MAP by VTC were generated to evaluate their ability to discriminate fluid responders from nonresponders. Results Of the 58 patients analyzed, there were 32 responders (55%) and 26 nonresponders (45%). The basic characteristics were comparable between the two groups (p > 0.05). The area under the curve (AUC) for ΔSV-VTC, ΔVTI-VTC, and ΔMAP-VTC to discriminate responders from nonresponders were 0.81 (95% CI: 0.68–0.90), 0.79 (95% CI: 0.66–0.89), and 0.56 (95% CI: 0.42–0.69). The best threshold for ΔSV-VTC was −16.1% (sensitivity, 78.1%; specificity, 84.6%); the best threshold for ΔVTI-VTC was −14.5% (sensitivity, 78.1%; specificity, 80.8%). Conclusion Tidal volume challenge–induced relative change of stroke volume and velocity time integral can predict fluid responsiveness in patients during one-lung ventilation. Clinical Trial Registration: Chinese Clinical Trial Registry, No: chictr210051310.